ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BURNOUT PADA KARYAWAN PERUM PERHUTANI KBM-IK GRESIK - Shofiyatun Nisa; Wasti Reviandani (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the factors that influence burnout among employees at Perum Perhutani KBM-IK Gresik. The research used a qualitative method with a phenomenological approach. Data collection techniques were carried out through interviews and documentation. Research informants were selected using purposive sampling, taking into account their direct involvement in work activities. The data obtained were analyzed through data reduction, data presentation, and conclusion drawing stages. The results of the study show that employee burnout is influenced by high workloads and pressure due to limited staffing levels, as well as the difficulty of employees approaching retirement age in adapting to a digital-based work system. These conditions lead to physical and mental fatigue, as well as a decline in job satisfaction. This research is expected to serve as material for evaluation and consideration for companies in formulating human resource management policies that pay more attention to employee welfare